Why Roger Federer is a GOAT: an account of sporting genius. Issue 3 (2nd September 2018) - Higgins, Joe
ABSTRACT: Why is Roger Federer a GOAT ('Greatest of All Time') of tennis? I argue that the correct response goes beyond statistics and style of play; instead, it is due to the fact that Federer embodies the qualities that typify sporting genius. More than merely being a developed or refined form of expertise, sporting genius relies on the notion of performative fit; that is, the capacity to express viable ways of succeeding within a given sport in virtue of one's cultivated history of biological and socio-cultural existence. In other words, a genius such as Federer perfectly fits the requirements of his sport and, moreover, is able to safeguard and shape this fit through his unique disposition to perform in certain ways. Performative fit provides the foundations for received traits of genius such as creativity, self-belief and risk-taking.